Food, energy, and water security sustainability; an asymmetric approach for achieving sustainable development goals - Umar Shuaibu Aliyu; Behiye Cavusoglu; Souad Hassanie; Sani I. Abba; Saad Sh. Sammen; Ozgur Kisi (Discover Sustainability)
Abstract The world has arguably identified both output and population growth over time. Thus, the demand for agricultural commodities such as biofuels and the prominent challenges associated with sustainable land use, water, and food development all play a significant role in the development process, as all countries strive to achieve the use of different approaches, such as convergence in output per capita, energy use, water availability, and food production, more safely and ecologically. Therefore, this study is led by Access and Neo-Malthusian theories to investigate the effects of food, energy, and water security sustainability for achieving sustainable development goals using annual data covering 1980 to 2020 to estimate the asymmetric autoregressive distributive lag approach. Accordingly, the results revealed that the effects of positive changes in food, energy, and water security on sustainable development differ significantly from those of negative changes. A 1% change in food production, water supply development, or industrial value addition has a significant positive impact on sustainable development; however, a 1% change in energy use and carbon emission, population growth, or depletion of natural resources has substantial adverse effects on sustainable economic development in both the short run and the long run in Nigeria. The findings also revealed that restoring equilibrium convergence to achieve 2030 SDGs requires 16.2% each year. The study recommends adopting innovative systems that control and help manage available human and natural resources in productive sectors and increase value-added and renewable energy production in Nigeria.